3D numerical simulation of hot airflow in the human nasal cavity and trachea. (August 2022) - Shamohammadi, Hossein; Mehrabi, Samrad; Sadrizadeh, Sasan; Yaghoubi, Mahmood; Abouali, Omid
Abstract: Background and objective: The primary function of the human respiratory system is gas and moisture exchange, and conditioning inhaled air to prevent damage to the lungs and alveoli. In a fire incident, exposed soft tissues contract and the respiratory system may be severely damaged, possibly leading to respiratory failure and even respiratory arrest. The purpose of this study is to numerically simulate hot airflow in the human upper airway and trachea to investigate heat and moisture transfer and induced thermal injuries. Methods: For analysis, the airflow is assumed to be laminar and steady, and simulations have been carried out at volume flow rates of 5 and 10 L/min, inlet temperatures of 70–240 °C, and relative humidity up to 40%. The mucous layer and surrounding tissues are incorporated into the conducting zone of the model. The blood perfusion is considered at different rates up to 5(Kg/m 3 .s) to regulate the temperature, and the vapor concentration is coupled with the energy equation. Results: The temperature and humidity distribution on the airway wall were calculated for all the studied conditions in order to find the mild and severe burn for different inhaled air temperatures. At the inlet temperatures of 70 and 100 °C, there are mild burns in several nasal cavity regions. At the higher temperatures of 160 and 200 °C, these areas suffer from severe burns and mild burns occur at the superior parts and nasopharynx. Rapid evaporation and tissue destruction will be observed if anyone breathes the 240 °C air. Conclusions: The results show that the hot inlet temperatures drop below 44 °C when passing through the upper airway, and the lower airway was not affected. Increasing the inlet temperature from 70 to 240 °C extends the burns from mild to severe and the affected areas from the beginning of the nasal cavity to the pharynx. Highlights: Breathing hot air flow ranging from 70 to 240 °C was simulated numerically. Blood perfusion rate and coupling of heat and moisture were considered. Severe burns occur when breathing hot air above 100 °C, mainly in the upper airway. The nasal cavity is contributed to heat absorption vastly. Despite breathing this hot air, the lower airway remains largely unaffected.